Application of the Hungarian Algorithm for Workforce Task Optimization in Mobile Device Repair Operations - Rumetna, Matheus Supriyanto; Lina, Tirsa Ninia; Karay, Jeni; Santoso, Agustinus Budi; Ferdinandus, Wiesje (CV.RIZANIA MEDIA PRATAMA, 2025)
An imbalance in task assignments within a business unit can decrease efficiency and extend job completion time. To address this issue, an optimization approach is required to allocate tasks effectively and minimize total working time. This study analyzes the application of the Hungarian Method to optimize employee assignments at Konter Bintang Sorong, aiming to achieve the most efficient mobile phone repair time. A quantitative approach was employed using the Hungarian algorithm implemented through POM-QM for Windows version 5. Data were collected through observation, interviews, and documentation related to repair durations for each task type. The findings show that the Hungarian Method produced the most efficient task allocation: employee Willi repaired connectors in 25 minutes, Aksa handled software issues in 60 minutes, and Fadli repaired LCD components in 10 minutes. These results indicate that the Hungarian Method effectively reduces average repair time and increases the number of devices serviced within a given period. Thus, it serves as an effective optimization tool for improving task distribution, operational efficiency, and customer satisfaction.